Facile Synthesis of Iron Oxide Nanoparticles and Their Antimicrobial Activity - Narendhar1, C.; Murugu Mohan Kumar2, K.; Rejitha3, M.; Karpanai Selvan4, B.; Selvapriya1, A.; Janani1, D. (Asian Journal of Chemistry, 2013)
In this work iron oxide nanoparticle has been synthesized by a simple wet chemical reduction using plant phytochemicals and their anti microbial activities were evaluated. The particles showed even size distribution and had anti microbial activity even in minimal concentrations. The resultant particles where analyzed by UV-visible spectroscopy and particle size analyzer by dynamic light scattering DLS and zeta potential measurement.